Nietsche EA, Teixeira E, Medeiros HP, organizers. Care-educational technologies: a possibility for the empowerment of the nurse? Porto Alegre (RS): Moriá; 2014 - Carvalho, Aline Tomaz de; Oliveira, Mariana Gonçalves de (Rev Rene, 2014)
For the researchers in technologies of/in Nursing, the following work was released ‘Care-educational Technologies: A possibility for the empowerment of the nurse?’ The initial interest for the elaboration of the book emerged from three organizers: Elisabeta Albertina Nietsche, doctor, nurse and professor of the Universidade Federal de Santa Maria, RS, Brazil; Elizabeth Teixeira, doctor, nurse and professor of the Universidade do Estado do Pará, Brazil; Horácio Pires Medeiros, nurse and master´s degree student of the Universidade Federal do Pará, Brazil. Besides these, there was the participation of other nurse authors and one food engineer.